Acquiring Funds from NFEP&WM by Religious Entities for Pro-environmental Activities - Michalski, Artur (Studia Ecologiae et Bioethicae, 2020)
Over the last 30 years, the National Fund for Environmental Protection and Water Management (NFEP&WM) has been the main source of funding investments and other pro-ecological activities in Poland in the following areas: protection and sustainable management of water resources, support for projects in the scope of low-emission and resource-efficient economy, including innovation; waste management; earth surface protection, geology and mining; atmosphere protection, including improving air quality; biodiversity protection, environmental monitoring, counteracting environmental threats, ecological education, expertise and scientific and research works. Priority programmes implemented by the National Fund for Environmental Protection and Water Management supporting activities aimed at environmental protection, whose beneficiaries may be Church organizations include: Environmental Education, Protection of Biological and Landscape Diversity, Energy-saving Construction Part 1) Reduction of Energy Consumption in Construction.